Sustainable development of eco-industrial parks in China: effects of managers' environmental awareness on the relationships between practice and performance. (15th January 2015) - Qu, Ying; Liu, Yakun; Nayak, Raveendranath Ravi; Li, Mengru
Abstract: As an important means of achieving sustainable development, eco-industrial parks have been given great significance at every level of Chinese governments, and as a result, they have made great strides in China. The increasing pressures of resource constraints and the need for environmental protection have made the achievement of optimal sustainable development performance crucial. Managers of eco-industrial park administrative committees, as decision makers and executors, have a pivotal role in the design, plan, and organization for the sustainable development of eco-industrial parks. Furthermore managers' environmental awareness is important when organizing environmental practices in their eco-industrial parks. This paper seeks to establish the value of the effects of managers' environmental awareness on the relationships between environmental practices and sustainable development performance by presenting an analysis of Chinese eco-industrial park projects. Using an empirical study, this paper first identifies the key environmental practices, directed by managers, which impact the sustainable development performance of Chinese eco-industrial parks. The moderating effect of managers' environmental awareness on the relationships between environmental practices and sustainable development performance is then developed. Our results show that instituting environmental norms for eco-industrial park enterprises, building industrial symbiosis, and providing guidance to key enterprises play significant roles in producing sustainable development performance for eco-industrial parks. Managers' environmental awareness is helpful in driving and transforming environmental practices into sustainable development performance. Our results also provide assistance for designing and implementing environmental practices for sustainable development, recruiting managers with higher environmental awareness, and training managers to improve their environmental awareness so that eco-industrial parks can achieve sustainable development performance. Highlights: Practices influencing EIPs' sustainable development performance (SDP) are identified. Instituting environmental norms has the strongest impact on SDP. The second strongest impact is by the variable of building industrial symbiosis. The least impact is by the variable of providing guidance to key enterprises. EIP managers' environmental awareness affects the transformation of practices into SDP.